Crash characteristics and patterns of injury among victims of road traffic crashes admitted to General Hospital, Moneragala, Sri Lanka - Tennakoon, V.; Gimhani, W.M.C.; Jayasingha-arachchige, S.; Wickramasinghe, A.R.; Yasawardene, S.G. (My University, 2016)
Attached

Objectives: To identify crash characteristics and patterns of injury among victims of rjoad traffic crashes (RTC) admitted to General Hospital, Moneragala. J Methods: A descriptive study was conducted among hospitalized victims of RTC to identify crash details, injury patterns and contributory factors for crash over a period of four months.A pre-tested questionnaire was filled interviewing the victim or bystander. Needed injury descriptions were adopted from the bed-head-tickets. Results: Out of 274 victims, 203(74%) were males and 71(26%) were females. Victims’ age ranged from one year to 78 years. The youth; 20-39 years comprised 54% of the sample. Motorcyclists and pillion riders were involved in majority (50%) of RTC. Skidding (34%) and head-on collision (30%) were the most common types of RTC. The commonest cause for RTC was high speed (36%). Nearly 2/3rd of the crashes occurred during the day (6am-6pm). Majority of the victims (51%) were brought to hospital by three-wheeler. Only 7% had received first-aid on site. The limbs (68%) and head, face and neck (48%) were the commonest body regions injured. Apart from the superficial injuries (76%), crush and fractures accounted for 30% and 26% of the injuries respectively. Minimal to maximal days of stay at hospital varied from one to 36 with a mean of 3. Restricted activities were experienced by many. 16% of victims were recommended physiotherapy for more than three months. Conclusions: Male youth riding on motorcycles were highly susceptible for RTC. Extremities were injured in majority of the victims causing long/short term limitations in domestic and social activities.